Effects of isometric resistance training on blood pressure and physical fitness of men - Flavio de Souza Araujo (Motriz: Revista de Educacao Fisica, 2018)
Abstract AIMS The present study aimed to investigate the effects of whole body isometric resistance training (IRT) on blood pressure (BP), strength and aerobic fitness. We also analyzed whether the effects of whole body isometric training compares to whole body dynamic resistance training (DRT). METHODS Twenty-nine pre-hypertensive sedentary males, aged between 40 and 60 years were divided into three groups: IRT (n = 10), DRT (n = 9), and Control (n = 10). Both programs involved whole body resistance training, and occurred for 12 weeks, three times/week, at an intensity of 60% of a dynamic one repetition maximum test (1RM). Before and after 12 weeks, 24 hours blood pressure monitoring, 1RM strength and aerobic fitness were assessed. RESULTS IRT reduced diastolic BP values during a 24-hour period and daytime. There was also a decrease in mean BP values during daytime (P<0.05). No interaction between time and group in systolic BP, diastolic BP, mean BP, heart rate and arterial stiffness index were observed (P>0.05). IRT increased strength and aerobic fitness when compared to Control group. However, these changes were lower than DRT regarding strength (DRT: ∆ = 43.1±10.6% vs. IRT: ∆ = 24.1±7.1% vs. CON: Δ = 4.2±11.5%; P<0.05) and aerobic fitness (DRT: ∆ = 22.9±10.7% vs. IRT: ∆ = 12.9±6.1% vs. CON: Δ = -2.1±7.4%; P<0.01). CONCLUSION Whole body IRT reduced diastolic BP and mean BP, however, the decrease was not different for the DRT group. IRT also increased strength and aerobic fitness, nevertheless, these changes were lower than after DRT.